Foreign language communicative competence of future and current specialists in the legal sphere, public administration and law enforcement agencies as a component of general professional competence - Баланаєва, Оксана Василівна; Баланаєва, О. В.; Balanaieva, Oksana V.; Мамонова, Олена Іванівна; Мамонова, О. І.; Mamonova, Olena I.; Дихта, Наталя Миколаївна; Дихта, Н. М.; Dykhta, Natalia M.; Арделян, Олена Вікторівна; Арделян, О. В.; Ardelian, Olena V. (Hradec Králové : AD ALTA, 2024)
У контексті глобалізації особливо важливою стає комунікативна компетентність юристів та поліцейських у іноземній мові. Така компетентність дозволяє краще розуміти осіб, коли вони не говорять рідною мовою адвоката або поліцейських. Дослідження спрямоване на виявлення випадків, коли комунікативна компетентність іноземної мови має особливе значення для юристів та поліцейських. Дослідження використовує аналіз, синтез, узагальнення та формально-структурні методи. У статті розглядається набір норм, що регулюють використання комунікативної компетенції іноземної мови юристами та поліцейськими у цивільних, кримінальних, адміністративних та економічних судових процесах. У дослідженні аналізується необхідність володіння другою, не рідною мовою на основі різних законодавчих актів, включаючи Конституцію України, Закон України "Про безпекову діяльність", Закон України "Про судову владу та статус суддів", Закон України "Про національну поліцію", Закон України "Про адвокатуру та юридичну практику" та Закон України "Про нотаріат". Позитивним аспектом кримінально-процесуального законодавства є вимога забезпечити компетентність перекладача, коли він бере участь у кримінальному провадженні. In the context of globalization, the foreign language communicative competence of lawyers and police officers becomes especially important. Such competence allows for a better understanding of the persons when they do not speak the native language of the lawyer or the police officer. The study aims to identify cases where foreign language communicative competence has a special significance for lawyers and police officers. The research employs analysis, synthesis, generalization, and formal-structural methods. The paper examines a set of norms regulating the use of foreign language communicative competence by lawyers and police officers in civil, criminal, administrative, and economic legal proceedings. The study analyzes the necessity of proficiency in a second, non-native language based on various legislative acts, including the Constitution of Ukraine, the Law of Ukraine "On Security Activities," the Law of Ukraine "On the Judiciary and the Status of Judges," the Law of Ukraine "On the National Police," the Law of Ukraine "On the Bar and Legal Practice," and the Law of Ukraine "On Notariate." A positive aspect of criminal procedural legislation is noted regarding the requirement to ensure the competence of a translator when involved in criminal proceedings.
Balanaieva O. Foreign language communicative competence of future and current specialists in the legal sphere, public administration and law enforcement agencies as a component of general professional competence / O. Balanaieva, O. Mamonova, N. Dykhta // Ad ALTA (Jornal of interdisciplinary research). – Hradec Králové : AD ALTA, 2024. – 14(1). – P. 177-180. Режим доступу: https://www.magnanimitas.cz/ADALTA/140139/papers/A_35.pdf
Keywords: Foreign language communicative competence; English language; Lawyer; Police officer; European Education Area